The pedagogy of consciousness : pathways to education reform for urban youth culture - Jack, Nadira, 1982- (Urban Education, Cultures and Communities Ser., 2020)
"Integrating experience and observations with theoretical ideologies and philosophical dispositions, the author provides a refreshing methodology and vision to the development of curriculum and instruction for administrative leaders, educators and policymakers in an urban education setting. Collectively combing her administrative and instructional experience as an educator, principal and superintendent, she shares with readers a new pedagogical approach that emphasizes principles of collaboration and co-investigation among educators and students to explore universal life lessons and confront systemic oppression that impact urban youth. The Pedagogy of Consciousness is one that emphasizes a humanizing approach to education with balanced partnerships and shared connections among educators and students. The promise of this compelling model is that it collectively revitalizes a broken, disenfranchised system, while demonstrating the capacity to revolutionize urban education and transform lives. The book opens up with a historical analysis of education, beginning with its inception and culminating with its present state of affairs, confronting systemic inequities and modes of standardization that still permeate today. The author provokes administrative leaders and educators to value student diversity and rethink the architecture of the traditional school systems by placing students at the forefront of their education through the co-development of curriculum and learning themes that impact their lives on a daily basis. The Pedagogy of Consciousness provides innovative measures for educators and students alike to recognize the excellence that they were born with. The model, which is based on the dynamic disposition of education as a fluid, organic process, highlights relationship building among educators and students as a core element necessary to create a classroom culture based upon facets of loyalty, trust and mutual respect. To this end, educators and students investigate issues that affect their lives on a daily basis to experience self-growth and liberation that ultimately transcends into a shift in perception, thoughts and action. Embedded in the model is also the use of coping mechanisms and daily affirmations that allow students to recognize the highest form of one's inner consciousness. The author demonstrates the importance of leading educational reform through teaching students that they are pillars of their own success"--